Ukrainian kharakternyky as an esoteric system of realization of personality - Matveev, V. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article raises a number of problems associated with self-realization of personality-the necessary basis for the development of any nation. For revival and development of Ukrainian national system of self-realization, the author turns to the phenomenon of the of the Cossacks at the same time pointing out that inside it always observed ideological differences between normal Orthodox Cossacks and with so-called Characterniki who professed esoteric doctrine of military magic, which has its origins in pagan religion. Analyzing the negative role of dual faith the author concludes that that this problem can be overcome only through the disclosure of esoteric potential of Paganism and Christianity.